2004
DOI: 10.1097/00129492-200405000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Findings in the Auditory Pathway of Patients With Sudden Deafness

Abstract: Enhanced MR imaging seems to be a useful examination in patients with SSNHL. The aim should not be only to exclude specific retrocochlear etiologies, but by appropriate techniques, MRI could reveal both peripheral and central abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 16 publications
1
31
1
1
Order By: Relevance
“…Most of the studies in this group identified patients prospectively. [2][3][4][5]11,[16][17][18][21][22][23][24][25][26] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies in this group identified patients prospectively. [2][3][4][5]11,[16][17][18][21][22][23][24][25][26] …”
Section: Resultsmentioning
confidence: 99%
“…MRI is the modality of choice for evaluation of the cochlea and auditory pathway in patients with SSNHL, being able to identify an etiology for SSNHL in a significant number of cases, 14,19,22,23 in particular, being helpful in the diagnosis of cerebellopontine angle tumors, inner ear anomalies, and SSNHLrelated CNS disease. MRI is superior to computed tomography (CT) imaging particularly for small intracanalicular tumors, but CT may be of some use when an MRI scan is contraindicated or when an abnormality of the bony inner ear is sought.…”
Section: Inner Ear and Cns Etiologymentioning
confidence: 99%
“…4,10,60,[96][97][98] Testing with MRI, ABR, or follow-up audiometry is important for detecting vestibular schwannoma because no clinical features can reliably distinguish SSNHL caused by an underlying tumor from the more common idiopathic variety. 4 Tinnitus in the affected ear prior to the onset of the SHL, associated otalgia, or paresthesias are more common in patients with vestibular schwannoma; however, these symptoms are too rare for their absence to reliably rule out a retrocochlear lesion.…”
Section: Risk Of Vestibular Schwannomamentioning
confidence: 99%
“…2 MR imaging is frequently performed to evaluate patients with SSNHL, traditionally to identify brain lesions or retrocochlear lesions such as vestibular schwannoma. 3 Several studies reported that new MR imaging sequences can evaluate labyrinthine abnormalities (the presence of intracellular and extracellular methemoglobin or increased protein content in the membranous fluid) by using 3D fluid-attenuated inversion recovery in patients with SSNHL 4-10 and can distinguish endolymphatic hydrops by volumetric quantification of MR imaging. 11 These abnormal findings may also be a novel prognostic factor for SSNHL, but there are conflicting results about the prognostic value of abnormalities on labyrinthine MR imaging.…”
mentioning
confidence: 99%